The Impact of Tax Avoidance, Tax Risk, Profitability, and Institutional Ownership on Cost of Debt - Hadiwibowo, Imam; Olivia Angie, Silvi; Taufik Azis, Mohammad (Global Financial Accounting Journal, 2024)
Purpose - This study intends to investigate the influence of tax avoidance variables, tax risk, profitability, and institutional ownership on debt costs. Research Method - This study uses 9 infrastructure firms listed on the Indonesia Stock Exchange (ISE) from 2019 to 2023 were examined using a purposive sampling method. The analysis for this study employed multiple linear regression modeling. Findings - The study findings indicate that tax avoidance and tax risk positively influence the cost of debt, whereas profitability and institutional ownership have no impact on it. Implication - Tax avoidance and tax risk affect the cost of debt as creditors view them as indicators of increased risk, leading to higher interest rates and additional monitoring expenses. Conversely, profitability and institutional ownership do not have a significant impact. These findings emphasize the necessity of effective tax risk management and governance to ensure financial stability and lower the cost of debt.